2012
DOI: 10.1177/0963721411429451
|View full text |Cite
|
Sign up to set email alerts
|

Self-Control and Aggression

Abstract: Psychological science has largely neglected the role of self-control in studying aggression. Fortunately, the past half decade has witnessed a surge of research on this long-neglected topic, including two self-control-informed integrative theories of aggression. Robust experimental evidence demonstrates that self-control failures frequently predict aggression and, conversely, that bolstering self-control decreases aggression. Research on rumination also suggests that maladaptive anger regulation decreases self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
220
1
17

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 279 publications
(245 citation statements)
references
References 19 publications
7
220
1
17
Order By: Relevance
“…Within the context of reactive aggression, both serotonin augmentation and behavioral self-control training lower aggressive outbursts (Denson, DeWall, & Finkel, 2012;Berman, McCloskey, Fanning, Schumacher, & Coccaro, 2009). These interventions may help people with the MAOA-L genotype better control aggressive responses.…”
Section: Discussionmentioning
confidence: 99%
“…Within the context of reactive aggression, both serotonin augmentation and behavioral self-control training lower aggressive outbursts (Denson, DeWall, & Finkel, 2012;Berman, McCloskey, Fanning, Schumacher, & Coccaro, 2009). These interventions may help people with the MAOA-L genotype better control aggressive responses.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, participants who had prayed for another person were better able to control their aggressive impulses than participants who had only thought about this person. From the perspective of the strength model of self-control, a provocation may be functionally equivalent to a resource depletion task in that it impairs self-control and is commonly associated with subsequent impulsive (aggressive) behavior (Denson, DeWall, & Finkel, 2012). Praying counteracted this effect of impaired self-control after provocation.…”
Section: Introductionmentioning
confidence: 99%
“…Since ego depletion may negatively affect the actual behavioral response in police-citizen encounters, it would be beneficial to focus on different strategies in order to mitigate these effects. First, the individual tolerance level can be bolstered by training (Denson et al , 2012Miles et al 2016). Denson et al (2012), for instance, showed that students who practiced self-control for 2 weeks by using their non-dominant hand for everyday tasks showed reduced anger when subsequently provoked by a fictitious fellow student.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…First, the individual tolerance level can be bolstered by training (Denson et al , 2012Miles et al 2016). Denson et al (2012), for instance, showed that students who practiced self-control for 2 weeks by using their non-dominant hand for everyday tasks showed reduced anger when subsequently provoked by a fictitious fellow student. Likewise, in line with the argument of training under operational constraints in order to foster skill transfer (Driskell et al 2008;Staller et al 2017;Wollert et al 2011), training under ego-depleted conditions may provide the individual with the experience to cope with this internal state while displaying optimal behavior.…”
Section: Practical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation